Demographic, Clinical, and Immunologic Features of 389 Children with Opsoclonus-Myoclonus Syndrome: A Cross-sectional Study - Pranzatelli, Michael R.; Tate, Elizabeth D.; McGee, Nathan R. (Frontiers in Neurology, 2017)
Pediatric-onset opsoclonus-myoclonus syndrome (OMS) is a devastating neuroinflammatory, often paraneoplastic, disorder. The objective was to characterize demographic, clinical, and immunologic aspects in the largest cohort reported to date. Cross-sectional data were collected on 389 children in an IRB-approved, observational study at the National Pediatric Myoclonus Center. Non-parametric statistical analysis was used. OMS manifested in major racial/ethnic groups, paralleling US population densities. Median onset age was 1.5 years (1.2 - 2 IQR), inclusive of infants (14%), toddlers (61%), and youngsters (25%). The higher female sex ratio of 1.2 was already evident in toddlers. Time to diagnosis was 1.2 months (0.7 - 3); to treatment, 1.4 months (0.4 - 4). Irritability/crying dominated prodromal symptomatology (60%); overt infections in < 35%. Acute cerebellar ataxia was the most common misdiagnosis; staggering appeared earliest among 10 ranked neurological signs (P < .0001). Some untreated youngsters had no words (33%) or sentences (73%). Remote neuroblastic tumors were detected in 50%; resection was insufficient OMS treatment (58%). Age at tumor diagnosis related to tumor type (P = .004) and stage (P = .002). A novel observation was that paraneoplastic frequency varied with patient age—not a mere function of the frequency of neuroblastoma, which was lowest in the first 6 months of life, when that of neuroblastoma without OMS was highest. The CSF leukocyte count was minimally elevated in 14% (≤ 11/cu mm) with normal differential, and commercially-screened serum autoantibodies were negative, but CSF oligoclonal bands and B cells frequency were positive (58% and 93%). Analysis of patients presenting on immunotherapy revealed a shift in physician treatment practice patterns from monotherapy toward multi-agent immunotherapy (P < .001); the number of agents/sequences varied. In sum, a major clinical challenge is to increase OMS recognition, prevent initial misdiagnosis, and shorten time to diagnosis/treatment. The index of suspicion for an underlying tumor must remain high despite symptoms of infection. The disparity in onset age of neuroblastoma frequency with that of neuroblastoma with OMS warrants further studies of potential host/tumor factors. OMS neuroinflammation is best diagnosed by CSF oligoclonal bands and B cells, not by routine CSF or commercial antibody studies.